Slow ethics and the art of care - Gallagher, Ann (Bingley, U.K. : Emerald Publishing Limited, 2020)
The path to good care-giving can be challenging, particularly where practices are characterised by crisis, moral panic and cultural complexity. How can we respond ethically when there is pressure to meet targets, work faster and implement quick, short-term fixes? This book offers a solution in the form of slow ethics.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Medical ethics; Caregivers -- Professional ethics; Medical -- Ethics; Medical ethics & professional conduct